2010
DOI: 10.1186/1471-213x-10-15
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 functions independently of SHH signaling and triggers cell condensation and apoptosis in regenerating axolotl limbs

Abstract: BackgroundAxolotls have the unique ability, among vertebrates, to perfectly regenerate complex body parts, such as limbs, after amputation. In addition, axolotls pattern developing and regenerating autopods from the anterior to posterior axis instead of posterior to anterior like all tetrapods studied to date. Sonic hedgehog is important in establishing this anterior-posterior axis of limbs in all tetrapods including axolotls. Interestingly, its expression is conserved (to the posterior side of limb buds and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 66 publications
6
54
0
Order By: Relevance
“…2D), thereby giving rise to the fin fold that will develop into the endoskeleton and dermal skeleton. Cartilage differentiation is observed in the expected bone formation area as soon as 9 days postamputation (dpa), closely analogous to what is observed during tetrapod limb regeneration (11). Precartilage condensations can be seen in histological slices, and the chondroblasts underneath can be distinguished by their sparse arrangements and the extracellular matrix surrounding them, whereas the apical mesenchymatous cells of the regenerate remain undifferentiated ( Fig.…”
Section: Resultsmentioning
confidence: 70%
“…2D), thereby giving rise to the fin fold that will develop into the endoskeleton and dermal skeleton. Cartilage differentiation is observed in the expected bone formation area as soon as 9 days postamputation (dpa), closely analogous to what is observed during tetrapod limb regeneration (11). Precartilage condensations can be seen in histological slices, and the chondroblasts underneath can be distinguished by their sparse arrangements and the extracellular matrix surrounding them, whereas the apical mesenchymatous cells of the regenerate remain undifferentiated ( Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Moreover, the expression of Bmp-2 and Sox-9 in urodeles correlates with chondrogenesis and the appearance of skeletal elements as described for other tetrapod taxa. Expression in later stages of limb development are also very similar to other tetrapods despite the absence of a paddle stage, with Bmp-2 expressed in the interdigital tissues where it was shown to be essential for giving anterior-posterior identity to digit primordia of other tetrapod taxa (Dahn and Fallon, 2000;Suzuki et al, 2008;Guimond et al, 2010).…”
Section: Developmentmentioning
confidence: 64%
“…Recently, Guimond et al (2010) investigated Bmp-2 expression in developing and regenerating limbs of Ambystoma mexicanum. They demonstrated that Bmp-2 and its target Sox-9 are independent of shh signaling in salamanders, corroborating studies on chicks that Bmp-2 is not a direct downstream target of shh involved in anterior-posterior patterning.…”
Section: Developmentmentioning
confidence: 99%
“…S7). Included among markers that were relatively unperturbed were Bmp2, normally associated with differentiation (28), and its downstream target AmTwist, a marker of dermal differentiation (29 Fig. 1.…”
Section: Mononuclear Phagocytes Regulate Regenerative Gene Expressionmentioning
confidence: 99%